Perkembangan Kognitif Anak Usia Dini Dan Permainan Ular Tangga - Nikmatur Rohmah; Eva Marisa; Fitrianti Wulandari (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
Cognitive development is a thought process, namely the individual's ability to relate, assess and consider an event. Cognitive processes are related to the level of intelligence that marks a person with various interests, especially in showing ideas and learning in everyday life. The purpose of this study was to determine factors related to cognitive. In addition, the research design was cross-sectional using a sampling technique using proportional random sampling. The dominant factor related to cognitive development in this study is learning in PAUD. Snakes and ladders game is a popular game among children. Snakes and ladders is a game in the form of a board that is divided into small boxes and several boxes depicting a number of ladders or snakes that connect with other boxes. Usually, this game is played by two or more children. The research to be solved is how to improve children's cognitive abilities through playing snakes and ladders in children. The type of research conducted is direct practical research in the classroom on children.